Combined Treatment of Heterocyclic Analogues and Benznidazole upon Trypanosoma cruzi In Vivo - Batista, Denise da Gama Jaén; Batista, Marcos Meuser; Oliveira, Gabriel Melo de; Britto, Constança Carvalho; Rodrigues, Ana Carolina Mondaine; Stephens, Chad E.; Boykin, David W.; Soeiro, Maria de Nazaré Correia (PLOS ONE, 2011)
Chagas disease caused by Trypanosoma cruzi is an important cause of mortality and morbidity in Latin America but no vaccines or safe chemotherapeutic agents are available. Combined therapy is envisioned as an ideal approach since it may enhance efficacy by acting upon different cellular targets, may reduce toxicity and minimize the risk of drug resistance. Therefore, we investigated the activity of benznidazole (Bz) in combination with the diamidine prodrug DB289 and in combination with the arylimidamide DB766 upon T. cruzi infection in vivo. The oral treatment of T.cruzi-infected mice with DB289 and Benznidazole (Bz) alone reduced the number of circulating parasites compared with untreated mice by about 70% and 90%, respectively. However, the combination of these two compounds decreased the parasitemia by 99% and protected against animal mortality by 100%, but without providing a parasitological cure. When Bz (p.o) was combined with DB766 (via ip route), at least a 99.5% decrease in parasitemia levels was observed. DB766+Bz also provided 100% protection against mice mortality while Bz alone provided about 87% protection. This combined therapy also reduced the tissular lesions induced by T. cruzi infection: Bz alone reduced GPT and CK plasma levels by about 12% and 78% compared to untreated mice group, the combination of Bz with DB766 resulted in a reduction of GPT and CK plasma levels of 56% and 91%. Cure assessment through hemocultive and PCR approaches showed that Bz did not provide a parasitological cure, however, DB766 alone or associated with Bz cured ≥13% of surviving animals.